Răspuns :
[tex]\overrightarrow{AB}\cdot \overrightarrow{AM} + \overrightarrow{BA}\cdot \overrightarrow{BM} = \\ \\ = \overrightarrow{AB}\cdot \overrightarrow{AM} +(-\overrightarrow{AB})\cdot \overrightarrow{BM} \\ = \overrightarrow{AB}\cdot \overrightarrow{AM} - \overrightarrow{AB}\cdot \overrightarrow{BM} \\ = \overrightarrow{AB}\cdot \Big(\overrightarrow{AM} - \overrightarrow{BM}\Big) \\ = \overrightarrow{AB} \cdot \Big(\overrightarrow{AM} - (-\overrightarrow{MB})\Big)[/tex]
[tex]= \overrightarrow{AB} \cdot (\overrightarrow{AM}+\overrightarrow{MB})\\ = \overrightarrow{AB} \cdot \overrightarrow{AB} \\ \\ = 2\overrightarrow{AB}[/tex]
=> Expresia nu depinde de M.
[tex]= \overrightarrow{AB} \cdot (\overrightarrow{AM}+\overrightarrow{MB})\\ = \overrightarrow{AB} \cdot \overrightarrow{AB} \\ \\ = 2\overrightarrow{AB}[/tex]
=> Expresia nu depinde de M.